Analisis Undang-undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan Di Tinjau dalam Kajian Politik Hukum - Arifuddin Muda Harahap (Universitas Islam Negeri Sumatera Utara, 2019)
UUD 1945 as the highest Indonesian constitution and consists of 16 chapters, 37 chapters, 194 paragraphs, 3 articles of transitional rules, and 2 additional rules. Legal political studies are a field of study reviewing both from the creation of new law and with the replacement of old law to achieve the purpose of the state. Act No. 13 of 2003 about employment is a result of the study of legal politics or a product of the Policy to address the employment problems in Indonesia. The method of research used is analytical diskriftif by reviewing legislation and normative review in the legal political level. From the results of the analysis of course Law No. 13 of 2003 on employment has a weakness among others are the highlights of article 52-54 of the work Agreement/contract of employment, article 64; 65; 66 about Outsourcing, sections 35 and 37 on recruitment and placement of work, section 78 on overtime, article 88-98 on the structure and scale of wages, article 108-115 on the company's regulation. Of course this law should be reviewed and updated in accordance with the study of legal politics. The government should review this labor law and see the Application of field